5th International Symposium on Tonal Aspects of Languages (TAL 2016) 2016
DOI: 10.21437/tal.2016-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Nonce-probe Tests and Auditory Priming to Investigate Speakers' Phonological Knowledge of Tone Sandhi

Abstract: Recent phonological research has shown that speakers may both overlearn and underlearn from lexical patterns of their language. This points to the importance of experimental studies to the construction of phonological analysis. In this paper, I explore the use of nonce-probe tests and auditory priming in the investigation of speakers' tacit knowledge of tone sandhi in a variety of Chinese dialects, with a particular focus on the effect of opacity on how speakers internalize the sandhi pattern. Nonce-probe resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…First, as previously mentioned, tone deletion is not attested in Mandarin or in Cantonese, which can minimize native language influence. Second, previous studies reported that tone sandhi patterns were not easily learnable in experimental settings (Zhang and Lai, 2010;Zhang, 2016;Zhang and Liu, 2016), which makes tone sandhi not an ideal testing site. For example, the nonce-probe tests conducted by Zhang (2016) showed that opaque Chinese tone sandhi patterns lacked full productivity and often failed to be applied to novel words.…”
Section: Tone Alternations In Mandarin 4 and In Cantonesementioning
confidence: 99%
See 1 more Smart Citation
“…First, as previously mentioned, tone deletion is not attested in Mandarin or in Cantonese, which can minimize native language influence. Second, previous studies reported that tone sandhi patterns were not easily learnable in experimental settings (Zhang and Lai, 2010;Zhang, 2016;Zhang and Liu, 2016), which makes tone sandhi not an ideal testing site. For example, the nonce-probe tests conducted by Zhang (2016) showed that opaque Chinese tone sandhi patterns lacked full productivity and often failed to be applied to novel words.…”
Section: Tone Alternations In Mandarin 4 and In Cantonesementioning
confidence: 99%
“…Second, previous studies reported that tone sandhi patterns were not easily learnable in experimental settings (Zhang and Lai, 2010;Zhang, 2016;Zhang and Liu, 2016), which makes tone sandhi not an ideal testing site. For example, the nonce-probe tests conducted by Zhang (2016) showed that opaque Chinese tone sandhi patterns lacked full productivity and often failed to be applied to novel words. And even a number of fully productive sandhi patterns in the lexicon in Tianjin were not easily learnable by Tianjin speakers (Zhang and Liu, 2016).…”
Section: Tone Alternations In Mandarin 4 and In Cantonesementioning
confidence: 99%
“…Recent studies of Chinese sandhi systems have been exploring the productivity of sandhi through nonce word (wug) testing (see e.g. Hsieh 1970;1975;1976;Zhang and Lai 2008;Zhang, Lai and Sailor 2009;Chuang, Chang, and Hsieh 2011;Zhang 2016;Zhang and Meng 2016, etc. ), with varying results.…”
Section: Productivity: Evidence From Alienable Nounsmentioning
confidence: 99%